The Relationship of Teachers Professional Performance to the Results of Athletics Championships in Middle Schools in Babil Governorate (International Journal of Psychosocial Rehabilitation, 2020)
The research problem was manifested by the researchers' work as a teacher of physical education and its presence and participation in organizing, preparing, and preparing competitions for external sports activities in various types of games. Notice that the professional performance of some teachers is not feasible and does not meet the aspirations of competitions and tournaments for the annual school sports organized by the Sports and School Activity Department in Babil Governorate. From here, the researchers decided to go into a changing study, which is the professional performance of physical education teachers, which plays an important and essential role in the results of athletic tournaments. In this context, the researchers raise questions: What is the level of professional performance of physical education teachers, and what is the relationship of the results of athletic championships to professional performance? For physical education teachers, the aim of the research is to identify the results of athletics tournaments for external sporting activities for the academic year 2018-2019 and to identify the professional performance of physical education teachers from the viewpoint of school principals in junior high schools in the province of Babel and identify the results of tournaments Saliva, foreign forces, sports activities, and their relationship with professional performance for teachers of physical education in junior high schools in the province of Babylon: the researchers assumed there is a relationship between the results of athletics championships, foreign sports activities, and professional performance for teachers of physical education in junior high school. The two researchers used the descriptive method in the survey method in addition to correlative studies, and the research community determined the principals of junior high schools, as they numbered 75 principals representing the districts and aspects of the Babylon Education Directorate distributed in the districts of the province and its areas, namely the Hilla District Center and the Hashemite District. The construction and preparation sample included (25) directors of athletics from the Directorate of Education for the province of Babylon and its districts. The application sample included (21) director of athletics from the Directorate of Education of Babylon Governorate and its district, and it was concluded from the research that the professional performance measure of (23) items prepared by the researchers on the sample has It achieved the desired goal, which is to measure the degree of the sample’s professional performance in the Hilla district and the Hashemite district, as the scale showed degrees ranging from good and very good to excellence of professional performance, and the results showed a correlation between professional performance and the result of matches for schools for the effectiveness of athletics to spend in Hilla as seen in the results, as there is no correlation between the professional performance as a result of the effectiveness of the games (athletics) to spend in the Hashemite.